Multi-Criteria Analysis of Selection Waste Management Development Strategy for Lubuk Binjai Landfill in Lubuk Linggau City - Fadiah Izzah Ajrina; Verlina Agustine; Shahnaz Nabila Fuady (Faculty of Engineering, Andi Djemma University, 2024)
Environmental sustainability is an urgent priority in dealing with waste management problems in Indonesian cities, one of which is Lubuk Linggau City. In the 2012-2032 Lubuk Linggau City RTRW, waste management standards have been set using the Controlled Landfill or Sanitary Landfill method, but in reality the Lubuk Binjai landfillstill adopts the Open Dumping method. This waste management not in accordance with environmentally sound waste management methods, so it is necessary to develop a waste management strategy for the Binjai Landfill. This research aims to identify priority strategies that can be applied in developing landfill waste management in Lubuk Linggau City using the Analytical Hierarchy Process (AHP) method. Data collection was carried out by conducting interviews with key informants who were managers of the Lubuk Binjai waste disposal site. Determination of criteria and sub-criteria based on previous literature studies and determination of alternative strategies based on the Lubuk Linggau City RTRW for 2021-2032. From the results of the analysis, it shows that the prioritized strategy is the Strategy for Improving Waste Management Methods Technology, with alternatives such as recycling processing, compost, and more sophisticated waste management technology such as controlled burning or anaerobic management. This is appropriate and crucial in overcoming problems at the Lubuk Binjai waste disposal site, that the Open Dumping method is still applied. It is hoped that the implementation of this strategy can bring positive and sustainable changes in waste management in Lubuk Linggau City.